Attacking inequality in the health sector : a synthesis of evidence and tools - Yazbeck, Abdo; World Bank (Washington, DC : World Bank, 2009)
The last 10 years have seen a resurgence in interest and research around inequalities in the health sector. While a disproportionate share of the new research has focused on measuring inequality in the health sector, work is emerging on how to understand the causes of inequality and on identifying successful approaches for tackling the problem. This book summarizes the operational lessons emerging from this new focus. It is intended to be an operational resource for change agents within and outside government in low and middle countries committed to improve access and use of critical health se.
An unacceptable reality -- Approaching a complex and persistent problem -- The importance of "listening" -- A menu of pro-poor policies -- Brazil, filling the cracks in universal coverage -- Cambodia: contracting with nongovernmental organizations to serve the poor -- Cambodia: health equity fund for the poor -- Chile: integrated services program for the poor -- Colombia: expanding health insurance for the poor -- India: community-based health care services -- Indonesia: health cards for the poor -- Kenya: expanding immunization reach through campaigns -- The Kyrgyz Republic: health financing reform and the poor -- Mexico: paying the poor to use health services -- Mexico: providing subsidized health insurance to the poor -- Nepal: participatory planning -- Rwanda: community-based health insurance -- Tanzania: social marketing for malaria prevention -- Vigilance.
BIBINDX
Keywords: Healthcare Disparities; Socioeconomic Factors; Health Status Disparities; Health Policy; Cross-Cultural Comparison; Developing countries